2003
DOI: 10.1093/clipsy/bpg046
|View full text |Cite
|
Sign up to set email alerts
|

The Role of African American Folk Beliefs in the Modern Therapeutic Process

Abstract: In response to a need for more cultural competency in indigenous practices, this article examines folk beliefs and healing practices in African American culture from theoretical, clinical, and practical perspectives. Four empirically derived culture-specific factors-spirituality, ritual, power of words, and dreams-are presented as themes often embedded in African American clients' narratives.A clinical case example illustrates the use of narrative therapy as an approach in therapy with a depressed client who s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The unique predictive value of spiritual well‐being is consistent with our understanding of the role spirituality plays in African American women’s lives. One reason for the strong association between spiritual well‐being and reasons for living relates to the culturally specific role spirituality plays in the African American community, and particularly, the southern African American community (Parks, 2003). Historically, African Americans have relied on their spirituality to cope with hardships and adversity (Boyd‐Franklin, 2010), and spirituality is an important cultural value in the African American female community (Mattis, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The unique predictive value of spiritual well‐being is consistent with our understanding of the role spirituality plays in African American women’s lives. One reason for the strong association between spiritual well‐being and reasons for living relates to the culturally specific role spirituality plays in the African American community, and particularly, the southern African American community (Parks, 2003). Historically, African Americans have relied on their spirituality to cope with hardships and adversity (Boyd‐Franklin, 2010), and spirituality is an important cultural value in the African American female community (Mattis, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This study is a secondary data analysis of the FORT Project (Wissing, Pretorius, & Heyns, 2000-2003 conducted as part of a broader project to clarify and advance the study of psychological well-being. The study employed an a posteriori cross-sectional research design to collect data.…”
Section: Methods Designmentioning
confidence: 99%
“…Spiritual distress results when life is not given meaning and is thus characterised by feelings of emptiness and despair (Frankl, 1959). Parks (2003) notes that spiritually based beliefs and practices provide strategies for finding solutions to life problems as well as peace of mind. Delgado (2005) conjectures that spiritually well individuals are capable of resolving the natural tension between that which is temporal and secular, and that which is transcendent by seeking to integrate the biological, social and psychological aspects of life.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…This also makes sense, because older individuals suffering from various chronic illnesses scoring high in TPT might view their GP as a person of trust, with whom individuals felt they could speak relatively freely, and not just as a health provider. 19 However, when weighing the plausibility of both explanation approaches, we concluded that the explanation approach mentioned first (external LOC) appears more plausible to us.…”
Section: Introductionmentioning
confidence: 83%